INDIVIDUALISATION OF STUDENTS’ LEARNING IN GRADES 5-8: EXPERIENCES OF TEACHERS - Braslauskienė, Rasa; Jacynė, Reda; Tolutienė, Gitana; Zubrickienė, Ilona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The article analyses the experiences of teachers in general education schools in the field of individualisation of students’ learning in grades 5–8. It theoretically discusses individualised learning strategies based on the guidelines of universal design for learning approach and teachers’ abilities in selecting approaches to individualise students’ learning. The implementation of individualised learning requires an increasing amount of theoretical and practical preparation of teachers in order to facilitate students' individualised learning. Teachers, therefore, need to explore innovative strategies and approaches to meet the broad and ever-changing learning needs of their students, to diversify their methods and to create dynamic learning experiences for their students. The analysis of the qualitative research findings has revealed that: teachers’ experiences of individualising students' learning are varied, conditioned by the ability to know the personal characteristics and abilities of the student; teachers’ experience of individualising teaching is characterised by a collaborative approach to dialogue and reflection; teachers’ insights into the strengths and weaknesses of their ability to individualise students' learning; and teachers’ insights into practical experiences of using the methods of individualisation.